Role of the NLRP1 inflammasome in skin cancer and inflammatory skin diseases - Calabrese, Laura; Fiocco, Zeno; Mellett, Mark; Aoki, Rui; Rubegni, Pietro; French, Lars E; Satoh, Takashi K (British Journal of Dermatology, 2024)
Inflammasomes are cytoplasmic protein complexes that play a crucial role in protecting the host against pathogenic and sterile stressors by initiating inflammation. Upon activation, these complexes directly regulate the proteolytic processing and activation of proinflammatory cytokines interleukin (IL)-1β and IL-18 to induce a potent inflammatory response, and induce a programmed form of cell death called pyroptosis to expose intracellular pathogens to the surveillance of the immune system, thus perpetuating inflammation. There are various types of inflammasome complexes, with the NLRP1 (nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-1) inflammasome being the first one identified and currently recognized as the predominant inflammasome sensor protein in human keratinocytes. Human NLRP1 exhibits a unique domain structure, containing both an N-terminal pyrin (PYD) domain and an effector C-terminal caspase recruitment domain (CARD). It can be activated by diverse stimuli, such as viruses, ultraviolet B radiation and ribotoxic stress responses. Specific mutations in NLRP1 or related genes have been associated with rare monogenic skin disorders, such as multiple self-healing palmoplantar carcinoma; familial keratosis lichenoides chronica; autoinflammation with arthritis and dyskeratosis; and dipeptidyl peptidase 9 deficiency. Recent research breakthroughs have also highlighted the involvement of dysfunctions in the NLRP1 pathway in a handful of seemingly unrelated dermatological conditions. These range from monogenic autoinflammatory diseases to polygenic autoimmune diseases such as vitiligo, psoriasis, atopic dermatitis and skin cancer, including squamous cell carcinoma, melanoma and Kaposi sarcoma. Additionally, emerging evidence implicates NLRP1 in systemic lupus erythematosus, pemphigus vulgaris, Addison disease, Papillon–Lefèvre syndrome and leprosy. The aim of this review is to shed light on the implications of pathological dysregulation of the NLRP1 inflammasome in skin diseases and investigate the potential rationale for targeting this pathway as a future therapeutic approach.